Architecture of Cities and the Politics of Abhorrence in Nigeria: a case of political neglect, abandonment and homelessness - Obiadi, Bons N. (Advances in Social Sciences Research Journal, 2020)
Architects, planners and engineers anchored firmly in the present, not able to resist good opportunities presented by the society. They are impulsive, do not plan or plan for tomorrow, impetient and in most cases, not caring about the growth, development and the people they are depriving of the basic needs to survive. The questions are, what are the reactions of the people in the building industry about Nigeria’s homelessness as we they no sence of succession and, what would they do about project abandonment by sitting govenors? This article draws attention to the colossal failure of the professionals in the building industry in providing adequate housing to eradicate homelessness and have not challenged the governors to complete the projects left by their predecessors. The instrument of more than two research strategies; quantitative and qualitative research methods and their tactics were used. Secondary data were based on direct observation and relevant documents from previous studies on the related matter. Most Nigerian politicians are idealogically incompetent with questionable competence executing their legisletive duties that, resulted in housing inadequacy and homelessness. The medical and psychological conditions of the homeless people should be the society’s primary concern and the recommendation of this paper. Architects are known for their graphic skills and communications, but they are not using them for the growth and development of the communities and they have derailed in the true objective and values of what should have been, the growth and development of the communities devoid of systemic inequality.